2007
DOI: 10.17796/jcpd.31.2.a20j230572178wp5
|View full text |Cite
|
Sign up to set email alerts
|

Oral-health Workshop Targeted at 0-5-yr. old Deprived Children's Parents and Caregivers: Effect on Knowledge and Practices

Abstract: One-session oral-health workshop was targeted at 770 parents and 60 caregivers of 0-5-year-old low-income children. Lower plaque scores (Silness & Löe-modified index) were observed in test-group-(TG) children after 1 and 6-months (Median=0) than control-group-(CG) (Median=1)(p<0.05), with a significant improvement from baseline among the TG (p<0.05). The questionnaire showed improvement in the TG parents/caregivers' knowledge after 1- 6-months regarding white-spot lesion visual recognition; w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 2 publications
0
33
0
4
Order By: Relevance
“…This case-cohort study showed that children whose mothers participated in the OHPP had significantly better oral health at the age of 5 than their peers whose mothers did not participate in the program. Comparable preventive programs support the success of health promotion at an early age (23)(24)(25)(26). Counseling of mothers of infants aged 6-18 months with motivating interviews for 1 year had a positive effect on the oral health of their children (18).…”
Section: Discussionmentioning
confidence: 99%
“…This case-cohort study showed that children whose mothers participated in the OHPP had significantly better oral health at the age of 5 than their peers whose mothers did not participate in the program. Comparable preventive programs support the success of health promotion at an early age (23)(24)(25)(26). Counseling of mothers of infants aged 6-18 months with motivating interviews for 1 year had a positive effect on the oral health of their children (18).…”
Section: Discussionmentioning
confidence: 99%
“…Vice versa, bottle feeding the baby influences the formation of the ogival palate as well as the formation of “crossbite”, a reduced opening of the back nasal cavity, and an increased incidence of sleep apnea. In addition, artificial feeding influences the possibility of the onset of arterial hypertension, obesity, cardiovascular illnesses, and inflammatory pathologies regarding oral mucous [23, 24]. …”
Section: Neonatal Diet and Oral Healthmentioning
confidence: 99%
“…For example, Colombian children at 2 years of age are entitled to a free first dental appointment. Further, children younger than 5 years are entitled to receive health education and fluoridation at no charge (12). Of course, promotion of frequent use of fluoridated dentifrices and adequate tooth brushing practices by oral health professionals and the parents of children is of great importance (13).…”
Section: Current Problems In Colombia Oral Health Carementioning
confidence: 99%